Deposit Insurance Systems : Addressing Emerging Challenges in Funding, Investment, Risk-Based Contributions and Stress Testing - Nolte, Jan P.; Khan, Isfandyar Z. (World Bank, Vienna, 2017)
The main public policy objectives of a deposit insurer are to reimburse depositors after bankfailure and to contribute to the stability of a financial system. To achieve these objectivesand to build public confidence in a deposit insurance system, deposit insurers musthave operational readiness to be able to act quickly after a bank failure. Sound fundingarrangements are essential aspects of such readiness, as they ensure prompt reimbursementof insured depositors and sufficient funds for the deposit insurer to unwind the institution.Depositor confidence depends, in part, on knowing that adequate funds for depositinsurance would always be available to ensure the prompt reimbursement of their claims. Itis therefore considered a best practice to build credible ex-ante funding mechanisms whichhave the financial capacity to ensure that these obligations are met.